REVIEW ON ARGYREIA SPECIOSA (L. f.) SWEET. (VRDHHADARU): PLANT OF INDIAN MEDICAL LEXICONS - Chhavi, *Yadav; Suresh, Chaubey; Tejbeer, Singh (International Journal of Ayurveda and Pharma Research, 2017)
Argyreia speciosa Sweet. is a popular Indian medicinal plant, which has long been used in traditional Ayurvedic Indian medicine for various diseases. It is commonly known as Vidhaara or Vrddhadaru. It is a large creeper and is covered with hair all over. Flowers are either pink or red or purple coloured. It is not mentioned in Samhitas, but described in the Nighantu granthas. Vrddhadaru is a controversial drug. It is mainly confused with Ipomaea petaloidea. In Nighantus it is described by name of Vrddhadaru. It is mainly described in Dhanvantri Nighnatu, Shodhal Nighantu, Abhidhan Ratnamala, Madanpal Nighantu, Raj Nighantu, Nighantu Adarsh and in Priya Nighantu. The Importance of Plant is well recognized by its presence in almost all Nighantus and by its therapeutic potential. Therapeutically prove action of Argyreia speciosa Sweet. Is in aphrodisiac, immunomodulatory, hepatoprotective, antioxidant, antiinflammatory, antihyperglycemic, antidiarrheal, antimicrobial, antiviral, antiulcer, anticonvulsant, analgesic and central nervous depressant activities. A wide range of phytochemical constituents have been isolated from this plant. Its seeds mainly contain eragine, isoeragine which has hallucinogenic properties. It is a comprehensive account of the Taxonomy, Synonyms, Vernacular names, Classical review, Properties, Controversy, Morphology, Microscopy of root, stem & leaf, Chemical constituents & their action, Indication, Part used, Dosage, Therapeutic usage, Formulations & Preparations and recent research findings which shows the importance of plant and help to gain knowledge about the plant.